2014
DOI: 10.1007/s10953-014-0208-x
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation Methods for AC Impedance Measurements Made with a Concentric Cylinder Cell on Solutions of High Ionic Strength

Abstract: Different extrapolation methods of AC impedance spectra measured in a conductance cell with concentric cylinder geometry have been evaluated at room temperature. This was undertaken because previous high temperature studies showed that the extrapolation method was one of the largest contributors to the uncertainty for molar conductivities at high concentrations: these high concentrations are needed to determine ion-pairing formation constants under hydrothermal conditions. This was done by measuring the impeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The performance of the two-electrode cell in EIS measurements showed non-standard featurea presence of an inductance element. Similar behavior of this cell was reported in [9] . The cell inductive response was described by constant phase element with inductance (LCPE).…”
Section: New High Temperature Data On Electrical Conductivity Of Aquesupporting
confidence: 88%
See 3 more Smart Citations
“…The performance of the two-electrode cell in EIS measurements showed non-standard featurea presence of an inductance element. Similar behavior of this cell was reported in [9] . The cell inductive response was described by constant phase element with inductance (LCPE).…”
Section: New High Temperature Data On Electrical Conductivity Of Aquesupporting
confidence: 88%
“…The measurements of HCl electrical conductivity were carried out in Wood's laboratory in a flow apparatus described in more detail elsewhere [9,14]. Electrochemical impedance spectroscopy (EIS) data were obtained in a two-electrode flow cell at the range 100 -20,000 Hz for aqueous solutions of HCl (10 -5 -10 -3 mol kg -1 ) at 298 -673 K and up to 28 MPa.…”
Section: New High Temperature Data On Electrical Conductivity Of Aquementioning
confidence: 99%
See 2 more Smart Citations
“…The details of the frequency-dependent measurements and the experimental uncertainty limits in Z Re (o) and Z Im (o) are discussed in ref. 16 and 18-22. Our previous studies 16,18,22 showed that, for our type of cell, an extrapolation of Z Re (o), according to the expression…”
Section: Ac Conductivity Flow Cell and Injection Systemmentioning
confidence: 89%